Comprendere il gesto violento: l’approccio narratologico - Ciappi, Silvio; Schioppetto, Giulia (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
The use of a frame of reference in a narrative key constitutes an innovative perspective in criminology and, above all, in its forensic application. The understanding of the “motives” of crime through the various narratives of the perpetrators, the victims, the justice system and society in general, allows us to delve into the complex phenomenology of the violent act. The main aim of the narrative criminology is, in fact, to listen and to carefully scrutinize criminal life histories in order to give meaning to the dark part of reality that – sometimes – takes the form of a violent act. Doing “narrative criminology”, therefore means going beyond a purely symptomatological and reductivistic conception of criminal action to focus on those “tears in the veil” in the plot of criminal life, that represent nothing more than a maladaptive ways of telling one’s own story.